IgG4-related Sclerosing Cholangitis Mimicking Cholangiocarcinoma Diagnosed by Endoscopic Ultrasound-guided Fine-needle Aspiration - Matsumoto, Ryotaro (Intern Med, 2019)
A 58-year-old man was referred for obstructive jaundice. Imaging modalities revealed the presence of multiple pancreatic tumors and the stenosis of the middle common bile duct due to a hypoenhanced localized tumor. The multiple pancreatic tumors were histopathologically diagnosed as autoimmune pancreatitis by endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). To differentiate between IgG4-related sclerosing cholangitis (IgG4-SC) and cholangiocarcinoma, we diagnosed the biliary tumor as IgG4-SC by EUS-FNA because of insufficient pathological materials obtained in a transpapillary manner. We herein report a case　of IgG4-SC diagnosed by EUS-FNA.